2009
DOI: 10.1017/s1368980009992801
|View full text |Cite
|
Sign up to set email alerts
|

Length of residence and obesity among immigrants in Spain

Abstract: Objective: Various studies in the USA and Canada have consistently shown a positive association between length of residence of immigrants and obesity. Studies in European countries have obtained less consistent results. The present work assesses the influence of length of residence on the frequency of obesity in immigrants in the city of Madrid, Spain. Design: We studied a sample of 7155 persons aged 18 years and over residing in the city of Madrid, who were was surveyed between November 2004 and May 2005. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…The variable length of residence in the host country was always defined using an interval scale, generally divided into recent (< 5 years) and long-term (> 15 years). Eleven 13,17,20,28,29,30,31,32,33,34,35 studies included all immigrant groups resident in the host country. Five studies 17,28,32,36,37 showed the increase in length of residence in the host country but did not stratify the results by immigrant group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The variable length of residence in the host country was always defined using an interval scale, generally divided into recent (< 5 years) and long-term (> 15 years). Eleven 13,17,20,28,29,30,31,32,33,34,35 studies included all immigrant groups resident in the host country. Five studies 17,28,32,36,37 showed the increase in length of residence in the host country but did not stratify the results by immigrant group.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven 13,17,20,28,29,30,31,32,33,34,35 studies included all immigrant groups resident in the host country. Five studies 17,28,32,36,37 showed the increase in length of residence in the host country but did not stratify the results by immigrant group. Another study 28 presented results by region of origin, concluding 44 Norway 2 2 1 0 1 ↑↑↑ * 0: non-randomized/convenience sampling; 1: randomized sampling (not national-based); 2: randomized sampling (national-based); ** 0: < 385 cases; 1: 385-1,000 cases; 2: > 1,000 cases; *** 0: Criteria not met (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The independent variable was place of birth categorized as native for those born in Spain, and immigrants for those born in a country with non-very high HDI in 2015 (Europe, Africa, Latin America and Asia). In addition, educational attainment was considered as an effect measure modifier and was categorized as primary education or less, secondary and graduate or higher education [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Most immigrants are coming from Latin America (38%; mainly from Ecuador, Colombia, Peru and Bolivia) Maghreb (14%; mainly from Morocco), sub-Saharan Africa (4%; mainly Senegal and Nigeria), Asia (7%; mainly China) and the rest of non-very high developed European Union countries (10%; mainly Romania). However, and despite this trend as well as the importance of place of birth and the migratory process as determinants of inequality [10], few studies have focused on obesity inequalities between immigrant and native populations in Spain [25,26]. Furthermore, the immigrant population usually has a lower level of education than the native population [27].…”
Section: Introductionmentioning
confidence: 99%